Targeting the Histone Methyltransferase Disruptor of Telomeric Silencing 1-Like Restricts Avian Leukosis Virus Subgroup J Replication by Restoring the Innate Immune Response in Chicken Macrophages - Chen, Shihao; Wang, Dedong; Liu, Yinyin; Zhao, Ruihan; Wu, Ting; Hu, Xuming; Pan, Zhiming; Cui, Hengmi (Frontiers in Microbiology, 2020)
Avian leukosis virus subgroup J (ALV-J), an oncogenic retrovirus, is known to cause immunosuppression and various types of cancer in chickens. Recent reports have shown that epigenetic changes in DNA and chromatin are widely implicated in the life cycle of diverse viruses, and reversal of these changes in host cells can lead to alterations in the propagation of viruses. In the present study, we found that DOT1L, a histone H3 lysine79 (H3K79) methyltransferase, was upregulated during ALV-J infection in chicken macrophage HD11 cells. Subsequently, we show that targeting DOT1L with a specific inhibitor can significantly decrease the ALV-J replication and viral production. By generating of DOT1L-knockout (KO) HD11 cells using the CRISPR/Cas9 system, we show that deletion of the DOT1L led to an increase in the induction of IFNβ and interferon-stimulated genes (ISGs) in HD11 cells in response to ALV-J infection. Importantly, we confirmed that ALV-J infection impaired the activation of the Melanoma Differentiation-Associated Protein 5 ( MDA5)-mediated-IFN pathway by suppressing the MDA5 expression, and knockout DOT1L rescued the expression of MDA5 and Signal Transducer and Activator of Transcription 1 (STAT1), both of which tightly control the antiviral innate immunity. Collectively, it can be deduced from the current data that blocking DOT1L activity or deletion of DOT1L can lead to ALV-J replication inhibition and restoration of the virally suppressed host innate immunity. Thus we suggest that DOT1L might be a potential drug target for modulating host innate immune responses to combat ALV-J infection.